Estudo da ação do laser de baixa intensidade sobre o recrutamento celular e os mediadores inflamatórios pulmonares na DPOC experimental em ratos - Alves, Wellington dos Santos (2015)
Introduction: One of the most common diseases in the present century, COPD (Chronic Obstructive Pulmonary Disease) has its mark on pulmonary inflammation, characterized by a number of cells such as macrophages, lymphocytes and neutrophils mainly degrading elastic fibers and release a series of inflammatory mediators that recruit other cells that act in defense in the lung. Objective: To develop a COPD model with passive inhalation of cigarette smoke in a 45 day period and promote the treatment of the disease with low-power laser. Methodology: the animals were organized into groups, control (breathing room air without cigarette smoke), the COPD group (45 days of passive inhalation of cigarette smoke) and Laser (45 days of passive inhalation + 15 days of application low power laser) .Results: Total and differential cell counts as well as histological and biochemical analysis shows the presence of COPD. Data from low-power laser-treated group shows that there was a reduction in the number of inflammatory cells and the concentration of the inflammatory mediators present in animal tissue in COPD. Conclusion: The passive inhalation of cigarette smoke for 45 days resulted in COPD, and the low-power laser was effective in the treatment because it took the reduction of inflammatory mediators and cells present in this lung disease.